Hospital service quality evaluation with IVIF-PROMETHEE and a case study - SENNAROĞLU, BAHAR; TUZKAYA, GÜLFEM; KALENDER, ZEYNEP TUĞÇE (ELSEVIER SCIENCE INC, 2019)
Measuring satisfaction of patients and understanding their perceptions are important for the hospital management to respond to customers' growing demands for acceptable quality of healthcare services. The main purpose of this paper is to present a methodology that can be used in the healthcare service quality evaluation. IVIF-PROMETHEE method is applied for service quality evaluation based on patients' views in a real-life case study of a public hospital in Istanbul and the results are compared with the results from IVIF-TOPSIS method. Interval Valued Intuitionistic Fuzzy (IVIF) set is considered an appropriate tool because of the complexity and vagueness of the evaluation of healthcare services. The evaluation of the quality level of the healthcare service provides detailed information about the effects of considered criteria as well as creates opportunities in implementing effective procedures to overcome service quality problems via analysing the patients' views. The proposed methodology can be a useful tool for hospital management.
Keywords: MCDM; IVIF-PROMETHEE; IVIF-TOPSIS; Healthcare service quality; HEALTH-CARE; DECISION-MAKING; SUPPLIER SELECTION; FUZZY PROMETHEE; SATISFACTION; SUPPORT; SYSTEM; MODEL